Transformasi Tema Penelitian Construction and Demolition Waste Berbasis Analisis Bibliometrika - Evy Kusumaningrum; Nurul Muyasaroh; Dedy Hariyadi (Environmental Insight Journal, 2026)
Construction and demolition waste (CDW) is a major contributor to global solid waste generation, increasing alongside rapid construction activities and building demolition cycles. Although scholarly publications on CDW have grown substantially, the long-term evolution of research themes, knowledge structure, and geographical contributions has not been systematically examined. This limitation constrains the identification of dominant research directions and emerging gaps relevant to sustainable construction practicesThis study aims to analyze the historical development, thematic structure, and research trends of CDW using a bibliometric approach. Data were collected from the Scopus database through a systematic search of titles, abstracts, and keywords, covering publications from 1980 to 2025. A total of 463 journal articles were selected for analysis. Descriptive bibliometric techniques were applied to examine publication growth and country contributions, while keyword co-occurrence and network analyses were conducted using VOSviewer and Bibliometrix to identify thematic clusters and topic evolution. The results indicate a significant increase in CDW research since 2017, with China emerging as the leading contributor, followed by Brazil, India, Spain, and Australia. Thematic mapping identifies three dominant clusters: technological approaches to CDW processing and recycling, material and environmental performance studies emphasizing recycled materials and life cycle assessment, and systemic research framing CDW within circular economy and sustainable development contexts. Trend analysis reveals a shift from conventional waste management toward resource optimization and sustainable construction integration. These findings provide a quantitative basis for future CDW research directions in civil engineering and construction management.